A NEEDS ANALYSIS OF UNIVERSITY LECTURERS IN AN IELTS® PREPARATION PROGRAM - Wawan Setiawan; Fikri Asih Wigati (Wiralodra English Journal, 2026)
The internationalization of higher education has increased the demand for English proficiency among university lecturers, particularly in English as a Foreign Language context. As an internationally recognized assessment, the International English Language Testing System (IELTS®) is widely required for academic mobility and professional advancement. This study investigated the target needs, learning needs, and preferred learning conditions of university lecturers enrolled in an IELTS® preparation program at the language center of a state university in West Java. A descriptive survey design employing a needs analysis framework was used. Data were collected through a structured questionnaire consisting of Likert-scale items and open-ended questions. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic categorization. The findings indicate that lecturers perceive all four IELTS® skills as essential but experience challenges related to accent comprehension, structured academic writing, spontaneous speaking, and time-managed reading. Participants expressed strong preferences for authentic materials, strategy-based instruction, individualized feedback, IELTS® simulation practice, and flexible learning arrangements. The study highlights the importance of needs-based IELTS® preparation tailored to the professional demands and learning characteristics of university lecturers.